2009
DOI: 10.1007/s10926-009-9219-7
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Loss at Work; Health-Related and Work-Related Factors

Abstract: Except for psychological complaints, workers with a longstanding health condition generally perform well while being at work. Nevertheless, the likelihood of taking sick leave is increased. Among work-related factors, psychosocial work characteristics have the strongest relation with productivity loss, mostly with performance while at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
81
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 15 publications
10
81
0
4
Order By: Relevance
“…In accordance with the findings from the current study, a recent study found that psychological health problems influenced work performance more than other chronic health problems (26). Another study that compared and examined similar health problems showed that psychological health problems had the strongest effects on work productivity and sickness absence as compared to other health problems (8). The strong effects of psychological health problems on work ability and produc- Leijten et al tivity at work could potentially be explained by clear presence of symptoms and complaints, whereas, for example, circulatory health problems may be diagnosed by a physician but be unaccompanied by perceivable symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with the findings from the current study, a recent study found that psychological health problems influenced work performance more than other chronic health problems (26). Another study that compared and examined similar health problems showed that psychological health problems had the strongest effects on work productivity and sickness absence as compared to other health problems (8). The strong effects of psychological health problems on work ability and produc- Leijten et al tivity at work could potentially be explained by clear presence of symptoms and complaints, whereas, for example, circulatory health problems may be diagnosed by a physician but be unaccompanied by perceivable symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that health is more inherent to work ability because work ability takes an individual's work demands and resources into account -good health is in itself a resource (7). Past studies have shown that poor health is a strong predictor of reduced work ability (2), but also that health problems relate to productivity loss at work (8,27). Our findings differ from these latter studies in that only two of the seven health problems were related to productivity at work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cross sectional research, associations were found between 'low performance at work' and age and poor general health [4]. Associations between several workrelated factors (among others job content) and 'low performance at work' in both bivariate and multivariate analyses were also observed.…”
Section: Discussionmentioning
confidence: 82%
“…For example, depressed workers reported greater experienced difficulties in time management, mental, interpersonal and output job demands [2,3]. Other research showed that poor health and multiple health problems were associated with low work performance [4].…”
Section: Introductionmentioning
confidence: 99%